Actions speak louder than words: Tournament angling as an avenue to promote best practice for pelagic shark fishing. (February 2016) - Heard, Matthew; Sutton, Stephen; Rogers, Paul; Huveneers, Charlie
Abstract: Social research can aid in understanding the behaviour of the general public or stakeholders towards natural resources. In the case of recreational fishing, social research aids in integrating anglers' knowledge and attitudes into management frameworks to increase the likelihood of the uptake of new management regulations. Tournament anglers were surveyed at game fishing competitions throughout New South Wales, Victoria, and South Australia between February 2012 and May 2013 to investigate their general beliefs around sharks and their behaviours when targeting pelagic sharks. Over half (55%) of the anglers interviewed practised catch and release of pelagic sharks. Of those, almost all (98%) asserted that they attempt to release sharks in good condition, but a large percentage of anglers (48%) did not use circle hooks that have been shown to increase post-release survival. Results showing some concordance between angler's beliefs and behaviours when targeting pelagic sharks suggest that anglers are cognisant of the functional role of sharks in the ecosystem and would be open to recommendations ensuring the long-term sustainability of recreational fisheries targeting pelagic sharks. Highlights: Tournament anglers have positive attitudes toward sharks. Catches of pelagic sharks by tournament anglers were dominated by Isurus oxyrinchus . Catch and release of pelagic sharks was common. Use of recommended gear for catch and releasing was not universal.